Islah Reconciliation in The Iddah Period as Resolution of Divorce based on Sigmund Freud's Perspective - Fuad, Anisul; Sugianto, Sugianto; Sumanta, Sumanta; Setyawan, Edy (Ridwan Institute, 2023)
Divorce is heavily influenced by emotional and psychological factors of husband and wife in litigation. Before the process of determining a divorce decision, Islamic law regulates reconciliation which can be a solution to divorce cases by trying to re-establish an understanding of husband and wife togetherness to be re-established. This study aims to explain the context of reconciliation as a resolution to divorce from Sigmund Freud's perspective. This research uses descriptive qualitative method. The results of the study show that the decision to divorce between husband and wife is often present due to the presence of ego in either husband or wife who feels the need to be understood but does not get reciprocity as expected. In addition, the decision to divorce is also influenced by basic human instincts that want to satisfy their desires, either with or without careful consideration. Therefore, islah reconciliation as a resolution is a wise step in which the path of islah reconciliation is carried out by raising the awareness of the husband and wife about the main purpose of marriage